EFEKTIVITAS PELATIHAN ASISTEN PRAKTIKUM DALAM MENINGKATKAN KOMPETENSI ASISTEN DI LABORATORIUM FISIKA FMIPA UNIVERSITAS BENGKULU - Suwardi Suwardi (Integrated Lab Journal, 2016)
The research has been conducted to evaluate the effectiveness of training activities lab assistant at the Laboratory of Physics, University of Bengkulu. Samples are 50 trainees, 2 instructors, and 2 technicians. Data collected by using observation, questionnaires, and interviews. The results showed that: 1) the planning of training activities has not been effective, 2) the appointment of instructors has not been effective, 3) implementation of the training has been effective, 4) evaluation of the training has not been effective, 5) follow up of evaluation results have not been effective, and 6) improving the competence of assistants linked to the task of understanding and oral communication is effective. However, upgrading the assistant of the operation of the equipment and understanding of the practicum material has not been effective. Results of this research recommend that laboratory management planning and evaluation of training in order to obtain feedback for improving or increasing the quality of the next training assistant.